2009
DOI: 10.1186/1756-9966-28-30
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability as a prognostic factor for survival in patients with metastatic renal cell carcinoma

Abstract: BackgroundIn experimental systems, interference with coagulation can affect tumor biology. We suggested that abnormal coagulation could be a negative predictor for response to immunotherapy and survival among patients with metastatic renal cell carcinoma (MRCC).MethodsTo address this issue, retrospective analysis of 289 previously untreated MRCC patients entering on institutional review board-approved clinical trials was conducted between 2003 and 2006. In addition, two groups of MRCC patients with (n = 28) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Our findings accord with previous studies addressing the clinical and prognostic significance of fibrinogen and D-dimer in cancer patients in general [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Regarding NSCLC patients specially, Sheng et al [32] found significantly increased risk of disease progression and death among patients with hyperfibrinogenemia, and Altiay et al [28] reported that elevated plasma levels of D-dimer were associated with decreased survival and a poor response to chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings accord with previous studies addressing the clinical and prognostic significance of fibrinogen and D-dimer in cancer patients in general [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Regarding NSCLC patients specially, Sheng et al [32] found significantly increased risk of disease progression and death among patients with hyperfibrinogenemia, and Altiay et al [28] reported that elevated plasma levels of D-dimer were associated with decreased survival and a poor response to chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, a growing body of evidence suggests the existence of a correlation between activation of coagulation and fibrinolysis and tumor angiogenesis, invasion, progression, and metastatic spread [9][10][11][12][13][14][15][16]. In clinical studies, many researchers have documented the relationship between hemostatic abnormalities and several malignancies, and various hemostasis markers associated with tumor staging and prognosis have previously been reported [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In lung cancer, plasma fibrinogen and D-dimer levels are associated with tumor pathological stage, response to therapy, and survival [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only 5 reports have recently demonstrated an association between the plasma fibrinogen levels and clinical features in RCC patients [9,10,11,12,13]. In a retrospective analysis of 289 previously untreated metastatic RCC patients, Tsimafeyeu et al [9] reported that the prevalence of hypercoagulability was associated with metastatic RCC, and that hypercoagulability determines worse survival and response to treatment for metastatic RCC.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of 289 previously untreated metastatic RCC patients, Tsimafeyeu et al [9] reported that the prevalence of hypercoagulability was associated with metastatic RCC, and that hypercoagulability determines worse survival and response to treatment for metastatic RCC. Xiao et al [10] found that preoperative plasma fibrinogen levels are elevated in patients with RCC with distant metastasis or lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation